2020
DOI: 10.1021/acs.jafc.0c00346
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the Study and Use of Seawater Vegetables

Abstract: As global soil salinization increases, halophytes that can grow in saline soils are the primary choice for improving soil quality. Some halophytes can even be irrigated with seawater and used as vegetables. These so-called seawater vegetables include those that can be planted on saline and alkali soils and some edible halophytes and ordinary vegetables that are salt-tolerant. The cultivation of seawater vegetables on saline soil has become a matter of increasing interest. In this review, we focus on the salt-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 109 publications
2
8
0
Order By: Relevance
“…This result may be attributed to its estrogenic activity, since the estrogen plays a critical role in maintaining pregnancy and facilitating fetal growth in rats . Similar results were previously obtained by using pig models . In this study, daidzein was supplemented in the rat diet after mating.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This result may be attributed to its estrogenic activity, since the estrogen plays a critical role in maintaining pregnancy and facilitating fetal growth in rats . Similar results were previously obtained by using pig models . In this study, daidzein was supplemented in the rat diet after mating.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies indicated that daidzein has the potential to improve the reproductive performance of a variety of animal species . In the present study, maternal daidzein supplementation not only increased the number of total viable fetuses but also increased the litter weight and the weight of individual viable foetuses.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Overview of the post-harvest processing of algae Algae historically have been largely wild-harvested from bodies of water, but the increased demand of these products has driven producers to cultivate algae in more controlled environments (see Figure 1E). If strategically implemented, commercial production can also be leveraged to remediate depleted waters, combat invasive algal species, and reduce the burden on natural algae in locations with decreasing wild populations of algae (Hart et al 2014, Li et al 2020). Freshly harvested algae can be stored prior to consumption, although the high moisture content of the seaweed necessitates immediate processing or addition of a preservative such as mineral salts (e.g., sodium chloride) to prevent growth of spoilage organisms (Wang, Zhang, and Fang 2019).…”
Section: A Ementioning
confidence: 99%
“…Many halophytes can be used as vegetables for human consumption [ 72 ]. Seawater vegetables are rich in protein, vitamins, and a variety of essential trace elements [ 73 ]. S. salsa grown on saline land, even in coastal areas, is widely used as a vegetable.…”
Section: Utilization Of Halophytesmentioning
confidence: 99%